How does the material variation of dynamic hip screw affect the cut-out risk in the treatment of intertrochanteric femoral fractures?. (2016) - Celik, Talip; Mutlu, Ibrahim; Ozkan, Arif; Kisioglu, Yasin
The material selection of dynamic hip screw (DHS) is not usually considered from the point of mechanical effects. In this study, the effects of the titanium alloy and stainless steel DHS was investigated in the cut-out risk of femur using finite element analysis (FEA). Intertrochanteric femur fracture (IFF) (31-A2 type according to AO classification) was created in the 3D femur model obtained from computer tomography images. The DHS model was inserted to the fractured femur model in two different positions (inferior and middle). The material properties of DHS were defined for the FEA. The force applied to the femoral head was determined according to the maximum value that is observed during walking. The results show that the safest model was obtained in the middle placement of titanium alloy DHS according to the safety factor. Consequently, the use of stainless steel DHS for IFF could cause higher failure risk of DHS than the use of titanium alloy DHS.